Spatial and Temporal Variations of Cockle (Cerastoderma spp.) Populations in Two Portuguese Estuarine Systems With Low Directed Fishing Pressure - Santos, Cátia; Cabral, Sara; Carvalho, Frederico; Sousa, António; Goulding, Thomas; Ramajal, João; Medeiros, João Paulo; Silva, Gilda; Angélico, Maria Manuel; Gaspar, Miguel B.; Brito, Ana C.; Costa, José Lino; et al. (Frontiers in Marine Science, 2022)
Cockles are amongst the most exploited bivalve species in Portugal, playing an important ecological and socioeconomic role in coastal ecosystems. Two sympatric species of cockles, Cerastoderma edule (Linnaeus, 1758) and Cerastoderma glaucum (Bruguière, 1789–1792) may co-occur in estuaries and coastal lagoons in mixed populations along the European Atlantic coast, namely in Portugal, France and the United Kingdom. The increasing importance of shellfish harvesting in Portugal requires a good knowledge of cockle stocks and temporal variability in stock levels to better inform sustainable management practices. Therefore, this study aimed at assessing spatial and temporal variations in cockle populations in two Portuguese estuarine systems where the species are exploited at low levels. Sampling was carried out using a clam dredge, covering the entire potential area of occurrence of cockles in the Tagus and Sado estuaries at around the same time of the year in each of the three sampling years (2015, 2018, and 2019). The abundance, spatial distribution and population structure of cockles were examined at each system. Moreover, several water and sediment parameters were measured to understand the influence of environmental conditions on the spatial distribution and abundance of cockles. The results obtained showed that cockles occur mostly in the intermediate areas of both estuarine systems and are more abundant in the Tagus estuary. Depth, average sediment grain size and the species Ruditapes philippinarum were the factors that better explained the probability of species occurrence. The population structure analysis indicated that natural mortality is constraining the cockle communities given the low abundance of adult individuals with marketable size in both estuaries. This study highlights the need for appropriate management measures to ensure the sustainability of these bivalve population stocks that have significant socioeconomic importance for local populations.